Carotid Embolectomy and Endarterectomy for Symptomatic Complete Occlusion of the Carotid Artery as a Rescue Therapy in Acute Ischemic Stroke - Curtze, Sami (S. Karger AG, 2011)
Emergency endarterectomy of an occluded internal carotid artery (ICA) has not been investigated as an option of rescue therapy for severe acute ischemic stroke in the era of intravenous (IV) thrombolysis treatment neither as a primary treatment nor after failed IV thrombolysis. Data from the pre-IV thrombolysis era are conflicting and therefore emergency endarterectomy has not been recommended. The number of patients reaching the emergency room within the IV thrombolysis time window has vastly grown due to advanced acute stroke treatment protocols. The efficacy of mechanical thrombectomy as a primary or add-on to IV thrombolysis therapy option is being actively investigated. We herein report 2 cases of acute ischemic stroke with computerized tomography (CT) angiography-documented occlusion of an ICA that were treated with emergency carotid endarterectomy and embolectomy to restore cerebral blood flow. Both cases presented with severe stroke symptoms and signs not responding to IV thrombolysis and showed severe CT-perfusion deficits mainly representing ischemic penumbra. Blood flow was surgically restored after 5 h of symptom onset. Both patients achieved a favorable outcome. We conclude that timely surgical approach of acute ICA occlusion after failed thrombolysis as a rescue therapy may be a viable option in well-selected patients.